ZigBee and LoRa based Wireless Sensors for Smart Environment and IoT Applications - Ali, Ayanle, I; Partal, Sibel Zorlu; Kepke, Salih; Partal, Hakan P. (IEEE, 2019)
A communication system, which employs ZigBee and LoRa communication protocols is designed, developed, and tested in this experimental paper. The designed system contains a central receiver unit with LoRa and ZigBee transceiver modules, a microcontroller, a wireless sensor card with temperature and humidity sensors, LoRa and ZigBee transceiver modules, and a relay unit. The relay in the sensor card can be remotely or cloud-based controlled, and the temperature and humidity data from the sensor can be sent to the central receiver unit by using the ZigBee or LoRa transceiver modules. The microcontroller was configured and programmed by using the evaluation version of STM32CubeMX and Kiel mu Vision Integrated Development Environment (IDE). PCB designs of the central receiver unit and the wireless sensor card were done by using DipTrace CAD software. Sub-components of the system were manufactured, assembled and tested for its functionality, communication efficiency and range. The practical design and reported results given here are beneficial to communication engineers for lowpower, long-range smart Internet of Things (IoT) system applications. Taking advantage of the complementing performances of ZigBee and LoRa wireless technologies, a diversified communication system with smart features is proposed, designed, and tested in a single IoT system.
Keywords: LoRa; ZigBee; IoT; Wireless Sensors; STM32; Energy & Fuels; Engineering